Hang on to your old cameras: For some purposes, film is still better than digital. - Linn, Charles; Kolleeny, Jane F. (Architectural Record, 2004)
Today, practically everybody uses digital technology to make and store photographic images. Others are made indirectly by scanning existing photographs or transparencies that were made in the old-fashioned way, using film. One doesn't need to buy film or have it processed by a lab. The type of film selected by a photographer certainly affects the sharpness of a photograph, as does the physical size of the film. Almost any mention of slides will bring up one application where digital photography has been quite successful in superceding film, and that is when they are used with presentation software like Microsoft Corp.'s PowerPoint and Apple Corp.'s new Keynote.